2020
DOI: 10.1002/ajmg.a.62025
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic paternally inherited NLGN4X deletion in a female with autism spectrum disorder: Clinical, cytogenetic, and molecular characterization

Abstract: Neuroligin 4 X‐linked (NLGN4X) is an X‐linked postsynaptic scaffolding protein, with functional role in excitatory synapsis development and maintenance, that has been associated with neuropsychiatric disorders such as intellectual disability, autism spectrum disorders (ASD), anxiety, attention deficit hyperactivity disorder (ADHD), and Tourette's syndrome. Chromosomal microarray analysis identified a paternally inherited, 445 Kb deletion on Xp22.3 that includes the entire NLGN4X in a 2.5 year old female (46,XX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Another major difference between these tools lies in the detection of in-frame insertions/deletions that comprised ~ 20% of the variants detected by either InterVar or TAPES, while such SNVs were discarded by Psi-Variant. We decided to exclude these variants from Psi-Variant because their clinical relevance has been demonstrated in several genetic disorders 38,39 but not in ASD [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Another major difference between these tools lies in the detection of in-frame insertions/deletions that comprised ~ 20% of the variants detected by either InterVar or TAPES, while such SNVs were discarded by Psi-Variant. We decided to exclude these variants from Psi-Variant because their clinical relevance has been demonstrated in several genetic disorders 38,39 but not in ASD [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroligins ( NLGNs ) are postsynaptic cell adhesion molecules that have critical functions in synapse maturation, and NLGNs are located on the human X chromosome, which is called NLGN4X [ 15 ]. It has been demonstrated that variants in NLGN4X are a potential pathogenic mechanism for male bias in autism spectrum disorder [ 16 , 17 ]. Otherwise, partial duplication of the NLGN4X gene (Xp22.32) is related to cognitive deficits [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another major difference between these tools lies in the detection of in-frame insertions/deletions that comprised ~20% of the SNVs detected by either InterVar or TAPES, while such SNVs were discarded by Psi-Variant. We decided to exclude these SNVs from Psi-Variant because their clinical relevance has been demonstrated in several genetic disorders [36,37] but not in ASD [38][39][40].…”
Section: Discussionmentioning
confidence: 99%